Prove the identity.

label Mathematics
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

(1-cos x ) ( 1 + cos x ) 

(divided by) 

cos^2x 

tan^2x. 

Oct 20th, 2017

Please note that:

(1-cos x)(1+cos x)=1-(cos x)^2=

=(sin x)^2

So, we have:

[(1-cos x)(1+cos x)]/[(cosx)^2]=(sin x)^2/(cos x)^2=(tan x)^2

Jan 24th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 20th, 2017
...
Oct 20th, 2017
Oct 20th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer